The Games People Played: Tavern Amusements and Colonial Social Relations - Roberts, Julia (Ontario History)

(untitled) (The Ontario Historical Society, 2010)
Play was serious business. By entertaining themselves in many ways in the many public houses of Upper Canada, tavern-goers defined and enacted the contours of social power in this colonial society. As we see them “throwing sticks and stones,” playing “sleight of hand tricks,” dancing jigs and “8 reels,” or “gambling and drinking around a large table,” we see that play was a defining part of a social world linked to the tavern. Play was a means through which tavern-goers bound themselves together, but a means also, and paradoxically, through which they could define social distance and cultural space.